Designing and Developing Yogic Chess Board Game for Adolescents to Teach Ashtanga Yoga An Innovative Learning Methodology - Kukreja, Manish; Gowda, Paran; Panwar, Poonam (JOURNAL OF INDIAN EDUCATION, 2022)
Chess is a two-player strategy board game, which has been used as a teaching tool for different subjects. With the help of innovatively designed and developed yogic chess game, the extract of Patanjali’s Ashtanga Yoga has been disbursed to the adolescents in a simplified, interesting and playful manner. The creatively designed chess board has been used to understand few positive and negative effects producing terms found in yoga philosophy. Its efficacy has been tested among 50 students of Government Senior Secondary School, village Khachrauli of District Jhajjar of Haryana, India. A multiple choice questionnaire comprising 50 questions related to Patanjali’s Ashtanga Yoga was designed and students’ responses were collected before and after the intervention of yogic chess game module, which included theory as well as practical. Pre- and post-test data was analysed by using paired ‘t’ test and found the t-value as –24.25, which is very much significant as the calculated p-value was found to be <0.0001. Benefit of the designed yogic Chess board game is that it may sharpen the brains with value education based on eight folds of Ashtanga Yoga at young age.